RELATIONSHIP BETWEEN INTERNAL MORPHOLOGY AND PHYSIOLOGICAL QUALITY OF Leucaena leucocephala SEEDS USING IMAGE ANALYSIS - Medeiros,André Dantas de (2019)
ABSTRACT The use of new methodological approaches and inclusion of non-destructive evaluations in determining the quality of forest seeds has proven to be of great importance for the development of forest production. The aim of this study was to evaluate the effectiveness of the use of a semi-automated tool for measurement of digital images obtained by the X-ray test in seed lots of Leucaena leucocephala and their relationship to seed physiological quality. Seeds were collected from five mother trees in Viçosa, MG. The study was performed through analysis of radiographic images of the seeds. It was determined the percentage of damaged seeds (predation and fungi) and measured: the area, perimeter, circularity, relative density, and integrated density of the seeds. After the X-ray test, a germination test was performed on the seeds, from which ten variables related to seed physiological quality were extracted, including a vigor index. The use of semi-automated measurement tools associated with the X-ray test was effective for evaluating the internal morphology of Leucaena leucocephala seeds, and the variables determined are related to seed physiological quality.